Evaluation of winged beans (Psophocarpus tetragonolobus) as an aquafeed ingredient on growth and enzymatic activity of java barb fish (Barbonymus gonionotus) - Astuti, Santika Dewi; Maulidina, Setya Arum; Nofreeana, Andri; Tartila, Shobrina Silmi Qori (Arwana: Jurnal Ilmiah Program Studi Perairan, 2024)
Evaluation of winged beans (Psophocarpus tetragonolobus) as an aquafeed ingredient on growth and enzymatic activity of java barb fish (Barbonymus gonionotus)